INTERPERSONAL COMMUNICATION PATTERNS IN FAMILIES BETWEEN CHILDREN AND PARENTS IN DANASRI LOR, CILACAP - Reni Widiyawati; Muhammad Ridwan (PROCEEDING AL GHAZALI International Conference, 2023)
This research is based on the many cases of bullying, juvenile delinquency, free sex that occur in teenagers. One of the factors that cause these things is the lack of attention and communication between children and parents. In the family, children and parents are a unity that builds the smallest group in society. Parents are obliged to build good communication patterns and always give advice and are open to receiving opinions and criticism from children. Corot Hamlet is one of the hamlets in Danasri Lor Village, there are several incidents of bullying, a lot of juvenile delinquency, and pregnancy outside of marriage. Research on communication patterns between children and parents in Corot Hamlet, Danasri Lor Village was conducted from July to August 2023 using qualitative research methods. The methods used are observation, interview, and documentation. The research will focus on three discussions, namely sex education, friendship in the school environment, and socialising outside the school environment. The results of research on 9 children aged 12-15 years (early adolescence) and 8 parents in Corot Hamlet show that communication patterns between parents and children about sex education have not been carried out optimally, parents only give advice and prohibitions when socialising with the opposite sex, for example not coming home late at night, not having physical contact, not dating. Children occasionally talk about friends and activities at school although there are still some who are more comfortable talking to friends at school. Regarding relationships outside the school environment, both parents and children have made a good agreement, children obey what parents advise, by maintaining relationships, choosing good friends, and asking permission from parents when going to play. Overall, the communication pattern that occurs in Corot Hamlet is the Authorative Communication Pattern.